A study of the traditional use of goats and their products, the Tutume Agricultural District, 1989-1990 - Thedford, T.R.; Worman, F.D.; Kelemogile, K.M. (Botswana Ministry of Agriculture, 1990)
Seventy-two goats belonging to four separate famers in Marapong village of the Tutume Agricultural District were divided into a treatment group consisting of 54 animals and a control group of 18 animals. The treated animals were given a sub-cutaneous injection of 200 micrograms of Ivermectin per kilogram of body weight after a blood sample was drawn. A packed cell volume (PCV) test was run on the blood samples. Additional PCV's were run on days 14, 28, and 56. There was a statistically significant increase in the PCV's of treated animals at day 28 and 56 post injection when compared to treated animals on day 0 and to the controls on day 56. It was concluded that animals treated with Ivermectin to remove live infestation, should be hardier and consequently be more resistant to disease problems and hopefully less prone to illness and death, especially at the end of the dry season when these animals are typically at their lowest physiological ebb, and are subject to many severe stresses.